The Effectiveness and Strategy of Aqidah Akhlak Teachers at MAUWH - Mohammad Saat Ibnu Waqfin; Farid Nur Rojab (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to determine the effectiveness and strategy of the Aqidah Akhlak subject teachers in the new normal era during the Covid-19 pandemic. The method used by researchers in this case is qualitative descriptive analysis. The subjects of this study were informants who provided data through interviews and cakevisioner questions. The informants in this study were the Deputy Chief of the MA Curriculum, KH. Abd Wahab Hasbulloh Tambak Rice and teachers of aqidah morals as well as kuevisioner questions given to students. The data analysis used in this research is descriptive analysis. This research results that learning has been very effective so far and the teacher's strategy in providing learning has gone well even though the pandemic situation is still ongoing both face-to-face and by distance learning. For distance learning, Madrasahs use Elma (Madrasah elrning) and also use the Google Meet platform application in the delivery of subject matter and the use of the WhatsApp platform as communication in learning. In face-to-face learning, Madrasahs divide students into day shifts and reduce face-to-face lessons and always apply health protocols while in Madrasah.